2018
DOI: 10.2355/isijinternational.isijint-2017-392
|View full text |Cite
|
Sign up to set email alerts
|

<i>De novo</i> Formation of PCDD/F during Sintering: Effect of Temperature, Granule Size and Oxygen Content

Abstract: Integrated iron and steel industry is the major industrial source of dioxins or, more precisely, of polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF). Their main source is the sintering plant (preparing iron ore fines as feed for the blast furnace) and EAF for steelmaking. The influence of temperature (300-600°C), feed granule size (4 fractions, from 0.5-1 to 4-8 mm) and oxygen content (5 to 15 vol.%) on PCDD/F-formation has been investigated during de novo tests, involving a feed composed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
(46 reference statements)
1
0
0
Order By: Relevance
“…In contrary, this study concluded that O2 levels played a critical role in the formation of PCDD/Fs during de novo synthesis. The results of the present study are consistent with those of Zhang et al[36], Potter et al[37], and Xu et al[38] indicating that both precursor formation and de novo synthesis play significant roles in the generation of PCDD/Fs within the post-combustion zone of a municipal solid waste incinerator. On the other hand, in oxygen-deficient conditions, chlorinated compounds may persist longer increasing the risk of PCDD/F generation.…”
supporting
confidence: 93%
“…In contrary, this study concluded that O2 levels played a critical role in the formation of PCDD/Fs during de novo synthesis. The results of the present study are consistent with those of Zhang et al[36], Potter et al[37], and Xu et al[38] indicating that both precursor formation and de novo synthesis play significant roles in the generation of PCDD/Fs within the post-combustion zone of a municipal solid waste incinerator. On the other hand, in oxygen-deficient conditions, chlorinated compounds may persist longer increasing the risk of PCDD/F generation.…”
supporting
confidence: 93%